EXAMINING THE POTENTIAL FOR SUSTAINABLE DEVELOPMENT OF RURAL AREAS, WITH PARTICULAR REFERENCE TO THE USE OF INDUSTRIAL HEMP - Kapás, György Ádám; Lőrinc, Balázs; Káposzta, József (Studia Mundi – Economica, 2022)
In recent years, the cyclical changes that have shaped our lives have inevitably confronted society with externalities that have restructured our health, our environment and our welfare. During the pandemic period, most members of society have valued their health and the importance of a liveable environment, the importance of a lifestyle with typical rural characteristics, and the development of liveable spaces, including the exploitation of alternative, sustainable architectural options. It is important to note that the triad of nature, society and economy can be defined as the basis for integrated rural development, where nature is set within society and within it the economy. Consequently, the natural dimension should be at the forefront of all the activities that influence economic processes. By respecting these rules, it is possible to create sustainable living communities. In order to create a healthy living environment, it is necessary to minimise negative ecological impacts and improve environmental conditions, applying the precautionary principle, which is also included in the objectives of sustainable urban management.Thanks to our climatic and ecological conditions, the possibility of economically growing and exploiting industrial hemp has been available in our country for centuries. However, in the first third of the 20th century, both at global and domestic level, the progress and technological development of the 'hemp economy' was made impossible by law, so that the cultivation and processing of this crop is lagging far behind the agricultural technology of today. Today, however, the revival and revitalisation of the industrial hemp industry seems to be taking place in a growing number of countries. In our study, we set out to investigate this direction of development.